2008
DOI: 10.1016/j.yexcr.2007.09.011
|View full text |Cite
|
Sign up to set email alerts
|

cAMP signaling induces rapid loss of histone H3 phosphorylation in mammary adenocarcinoma-derived cell lines

Abstract: The phosphorylation of histone H3 is known to play a role in regulation of transcription as well as preparation of chromosomes for mitosis. Various signaling cascades induce H3 phosphorylation, particularly at genes activated by these pathways. In this study we show that signaling can also have the opposite effect. Activators of cAMP signaling induce a rapid and potent loss of H3 phosphorylation. This effect is not mediated through a cAMP metabolite since a membranepermeable form of AMP had no effect on H3 pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…Based on the fact that changes in the cellular expression profile are required to achieve the G1 block, it is possible that the function of the reversible cAMP-mediated disruption to G2 progression is to allow time for these changes to occur so that the cells efficiently arrest in G1 after mitosis. This is supported by our previous results showing that asynchronously-cycling cells treated with 8-Br-cAMP for 48 hours undergo only one division while untreated cells increase in number by a factor of 5 [37]. …”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…Based on the fact that changes in the cellular expression profile are required to achieve the G1 block, it is possible that the function of the reversible cAMP-mediated disruption to G2 progression is to allow time for these changes to occur so that the cells efficiently arrest in G1 after mitosis. This is supported by our previous results showing that asynchronously-cycling cells treated with 8-Br-cAMP for 48 hours undergo only one division while untreated cells increase in number by a factor of 5 [37]. …”
Section: Discussionsupporting
confidence: 80%
“…Our previous study showed that prolonged cAMP signaling results in a block to both G1 and G2 progression and significantly inhibits cell growth [37]. Here we show that the disruption of G2 progression occurs prior to the block to G1 progression.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations